Efficacy of Intravenous Magnesium Sulphate in Children Admitted with Severe Acute Bronchiolitis - Yasin, Tahira; Javeed, Asif (Indus Journal of Bioscience Research, 2025)
Background: Acute bronchiolitis ranks among the top causes of respiratory distress in children, and current options for treatment are limited. Magnesium sulfate has been proposed as a possible treatment based on bronchodilator as well as anti-inflammatory effects. Yet, in children with severe acute bronchiolitis, the efficacy of the drug is still in question, especially when compared with a placebo. Objective: To determine the efficacy of intravenous magnesium sulphate compared to placebo in children admitted with severe acute bronchiolitis. Study Design: Randomized controlled trial. Duration and Place of Study: This study was conducted from August 2023 to February 2024 at the Department of Pediatric Medicine, Ibn-e-Siena Hospital, Multan. Methodology: A total of 98 children aged 2 to 24 months with severe acute bronchiolitis were enrolled. Children were randomly assigned to either receive a single intravenous dose of magnesium sulfate (75 mg/kg, maximum 2 grams) or a placebo (0.9% saline). The primary outcome was the change in Wang clinical severity score after 24 hours, with secondary outcomes including hospital stay duration and response rate. Results: In this study, Group A (magnesium sulfate) showed significantly lower Wang scores at 24 hours (3.88 ± 0.88) compared to Group B (placebo) (4.69 ± 1.04), with a treatment response rate of 83.7% in Group A compared to 44.9% in Group B (p < 0.001). Age, gender, symptom duration, and initial severity were all significant factors influencing the treatment's efficacy. Conclusion: Intravenous magnesium sulfate significantly improves clinical outcomes and shortens hospital stay in children with severe acute bronchiolitis.